Inorganic nanoparticles : synthesis, applications, and perspectives - Altavilla, Claudia; Ciliberto, E. (Enrico) (Boca Raton, FL : CRC Press, 2011)
'Among the various nanomaterials, inorganic nanoparticles assume a special place because they are cheaper than others and easier to synthesize in the laboratory and mass produce. This text captures the current advances and fundamentals of synthesis, characterization, and application development of these materials. Topics discussed include magnetic materials, oxide thin films, solid state lighting, semiconductor nanoparticles for light emitting devices, solar energy, energy storage devices, and quantum dots in biomedicine. Highlighting the vast scope of applications, the book features contributions from an array of experts at the top of their fields'--Provided by publisher.
Includes bibliographical references and index.
Keywords: Nanoparticles